A hospital-centered approach to improve emergency obstetric care in South Sudan. Issue 1 (January 2015) - Groppi, Lavinia; Somigliana, Edgardo; Pisani, Vincenzo; Ika, Michelina; Mabor, Joseph L.; Akec, Henry N.; Nhial, John A.; Mading, Michel S.; Scanagatta, Chiara; Manenti, Fabio; Putoto, Giovanni
Abstract: Objective: To assess provision of emergency obstetric care (EmOC) in Greater Yirol, South Sudan, after implementation of a hospital-centered intervention with an ambulance referral system. Methods: In a descriptive study, data were prospectively recorded for all women referred to Yirol County Hospital for delivery in 2012. An ambulance referral system had been implemented in October 2011. Access to the hospital and ambulance use were free of charge. Results: The number of deliveries at Yirol County Hospital increased in 2012 to 1089, corresponding to 13.3% of the 8213 deliveries expected to have occurred in the catchment area. Cesareans were performed for 53 (4.9%) deliveries, corresponding to 0.6% of the expected number of deliveries in the catchment area. Among 950 women who delivered a newborn weighing at least 2500 g at the hospital, 6 (0.6%) intrapartum or very early neonatal deaths occurred. Of 1232 women expected to have major obstetric complications in 2012 in the catchment area, 472 (38.3%) received EmOC at the hospital. Of 115 expected absolute obstetric indications, 114 (99.1%) were treated in the hospital. Conclusion: A hospital-centered approach with an ambulance referral system effectively improves the availability of EmOC in underprivileged remote settings.